A Real-Time PCR Assay for Detection of Low Pneumocystis jirovecii Levels - Ruiz-Ruiz, Susana; Ponce, Carolina A.; Pesantes, Nicole; Bustamante, Rebeca; Gatti, Gianna; San Martin, Viviana; Gutierrez, Mireya; Bórquez, Pamela; Vargas, Sergio L.; Magne, Fabien; Calderón, Enrique J.; Pérez-Brocal, Vicente; et al. (Frontiers in Microbiology, 2022)
Here we report a new real-time PCR assay using SYBR Green which provides higher sensitivity for the specific detection of low levels of Pneumocystis jirovecii. To do so, two primer sets were designed, targeting the family of genes that code for the most abundant surface protein of Pneumocystis spp., namely the major surface glycoproteins (Msg), and the mitochondrial large subunit rRNA (mtLSUrRNA) multicopy gene, simultaneously detecting two regions. PCR methods are instrumental in detecting these low levels; however, current nested-PCR methods are time-consuming and complex. To validate our new real-time Msg-A/mtLSUrRNA PCR protocol, we compared it with nested-PCR based on the detection of Pneumocystis mitochondrial large subunit rRNA (mtLSUrRNA), one of the main targets used to detect this pathogen. All samples identified as positive by the nested-PCR method were found positive using our new real-time PCR protocol, which also detected P. jirovecii in three nasal aspirate samples that were negative for both rounds of nested-PCR. Furthermore, we read both rounds of the nested-PCR results for comparison and found that some samples with no PCR amplification, or with a feeble band in the first round, correlated with higher Ct values in our real-time Msg-A/mtLSUrRNA PCR. This finding demonstrates the ability of this new single-round protocol to detect low Pneumocystis levels. This new assay provides a valuable alternative for P. jirovecii detection, as it is both rapid and sensitive.